THE ESSENCE OF THE RESEARCH POTENTIAL OF GIFTED STUDENTS IN HIGHER EDUCATION INSTITUTIONS (Academicia Globe: Inderscience Research, 2023)
Identification of talented students in our republic and development of social and pedagogical technologies of their trainings. The regulatory framework for ensuring State and non-state cooperation in the field of education and the development of talented students has been created. The Presidential schools were created with the aim of deepening the disciplines, improving the effectiveness of teaching and developing high school students. Their material and technical base was provided. In the strategy of further development of the Republic of Uzbekistan, the priority task was defined as "to raise a generation of highly educated and intellectually developed people, to create a reserve of scientific and pedagogical personnel with competencies in higher educational institutions". As a result, the identification of talented students will allow them to enter the world of science, using a wide range of technologies to improve the competence of researchers based on innovative approaches.